Pengaruh Pemahaman Akuntansi, Digitalisasi UMKM dan Inklusi Keuangan Terhadap Kualitas Laporan Keuangan dengan Efikasi Diri Sebagai Variabel Mediasi - Martinus Budiantara; Hwihanus Hwihanus (Jurnal Perilaku dan Strategi Bisnis, 2024)
The purpose of this study is to find: (1) The Influence of Accounting Understanding and Financial Inclusion Partially on the Quality of Financial Statements. (2) the effect of Accounting Understanding on the quality of MSME financial statements mediated by self-efficacy. (3) the effect of MSME digitization on the quality of MSME financial reports mediated by self-efficacy. (4) the effect of MSME financial inclusion on the quality of MSME financial statements mediated by self-efficacy. The methodology used in this study is quantitative. The research sample is 103 MSME entrepreneurs in Sleman, Special Region of Yogyakarta. The data was processed using the SmartPLS method The results of the study showed that Accounting Understanding had no effect on the Quality of MSME Financial Statements, MSME Financial Inclusion had a significant effect on the Quality of MSME Financial Statements in Sleman. Self-efficacy is not able to mediate the relationship between Accounting Understanding and Financial Inclusion on the Quality of Financial Statements, but it cannot mediate the relationship between MSME Digitalization and Financial Report Quality.